The Influence Of Influencer Marketing On Gen Z Consumer Purchase Interest a Literature Review - Dian Natari; Rade Juliman Lumbantoruan; Dwi Sakinah; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
The purpose of this study is to determine the literature review on Influencer marketing and product quality on the purchase intention of generation Z consumers. Advances in internet technology have led to shifts in human lifestyles, especially in purchasing patterns. In writing this article, literature review plays an important role in formulating research ideas, understanding previous findings related to the topic, and identifying gaps in existing knowledge.A systematic literature review (SLR) was conducted in two well-known databases, ScienceDirect and Scopus. After applying the inclusion and exclusion criteria, 1,498 out of 2,036 articles were assessed as relevant, after which these papers were carefully examined to produce an in-depth analysis of the subject. Ultimately, 13 papers were selected for in-depth examination in the study. Based on SLR data, the articles were written between 2021 and 2024. The research methodology used in this paper includes descriptive analysis and bibliographic analysis.The results of writing the article are known that Influencer marketing is one of the company's strategies in achieving their strategic goals by utilizing influencers as messengers for products or brands so that they can reach a wider market.Brand is the identity of a company, where companies build a good brand image so that potential consumers can remember the good image of a product and stick to potential consumers.The results of this study show that many factors influence consumer behavior, including the role of influencers, product quality, and social media marketing strategies.